DETERMINAN PENGUNGKAPAN EMISI KARBON PADA PERUSAHAAN SEKTOR INDUSTRI: SUDUT PANDANG TEORI STAKEHOLDER - Athallah Yuniharto, Juan Daffa; Utami, Rizki Hanifah; Fayliencent, Ignatz Novrian; Hatta, Atika Jauharia (Universitas Sarjanawiyata Tamansiswa, 2024)
The purpose of this study was to examine the effect of profitability, company size, and independent commissioners on carbon emission disclosure in industrial sector companies listed on the Indonesia Stock Exchange (IDX) in 2018-2021. This research used the proportion of independent commissioners as a proxy for good corporate governance (GCG), total assets as company size, and return on assets as a measure of company profitability. The sampling method was carried out using purposive sampling and 30 companies were obtained from 2018 to 2021, and obtained 104 observations. Using panel data regression analysis, the results show that profitability has a positive influence on carbon emissions disclosure, but not company size and good corporate governance. The results indicated that companies with high profitability tend to have sufficient funding to cover the costs incurred when reporting carbon emissions, so they tend to report more carbon emissions than companies that have low profitability. The results shown support evidence for Stakeholder theory.